Energy Consumption as a Measure of Energy Efficiency and Emissions in the MENA Countries: Evidence from GMM-Based Quantile Regression Approach - Alkhawaldeh, Bashar Younis Subeih; Al-Zeaud, Hussein Ali; Almarshad, Mohammad Nassar (International Journal of Energy Economics and Policy, 2022)
Efficient efficiency of energy resources has been shown to have positive effects on both GDP growth and GHG emissions. While the negative effects of climate change and pollution continue to worsen, there has been a global slowdown in the rate at which energy efficiency is improving. In the Middle East and North Africa (MENA), carbon dioxide (CO2) emissions can be considerably influenced by economic and energy consumption. Therefore, the purpose of this research is to apply the generalized method of moments based on a quantile regression approach (GMMQR) to data for CO2 emissions, energy efficiency, real income, and research and development in MENA from 1990 to 2021 in order to determine the factors that determine CO2 emissions under the environmental Kuznets curve (EKC) framework. Overall, the data showed that energy efficiency had a 3.2% impact on emissions reduction across all quantiles. In order to achieve their goals of lowering emissions and strengthening energy security, MENA states must increase the efficiency with which they use petroleum. Energy efficiency policies may have rebound effects, which might reduce their efficiency, according to this study.